2017
DOI: 10.1515/jbcpp-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the GABA-ergic pathway in the anticonvulsant activity of the roots bark aqueous extract of Anthocleista djalonensis A. Chev. (Loganiaceae)

Abstract: The effects of Anthocleista djalonensis suggested the presence of anticonvulsant properties that might involve an action on benzodiazepine and/or GABA sites in the GABAA receptor complex or by modulating GABA concentration in the central nervous system (CNS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The active fractions significantly reduced the number of seizures and ameliorated behavioural seizures in pentylenetetrazole-challenged mice. These results are similar to those reported in our previous research in which Anthocleista djalonensis extracts protected mice against seizures induced by pentylenetetrazole [ 27 ]. Pentylenetetrazole-induced kindling is an experimental model of epilepsy in which chronic chemostimulation of the central nervous system pathway induces a spontaneous hyperexcitable state (kindling and fully kindled seizures, as well as spike waves epilepsy) and well-established generalised tonic-clonic seizures, providing a good evidence to study epileptic disorders [ 10 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The active fractions significantly reduced the number of seizures and ameliorated behavioural seizures in pentylenetetrazole-challenged mice. These results are similar to those reported in our previous research in which Anthocleista djalonensis extracts protected mice against seizures induced by pentylenetetrazole [ 27 ]. Pentylenetetrazole-induced kindling is an experimental model of epilepsy in which chronic chemostimulation of the central nervous system pathway induces a spontaneous hyperexcitable state (kindling and fully kindled seizures, as well as spike waves epilepsy) and well-established generalised tonic-clonic seizures, providing a good evidence to study epileptic disorders [ 10 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several mechanisms underlying such effects of Anthocleista djalonensis were previously proposed [ 27 ]. There were two such mechanisms: (1) Anthocleista djalonensis enhances gamma-aminobutyric acid (GABA)-mediated inhibition, reduces repetitive firing, and reduces both inhibition and excitation in neuronal networks and (2) Anthocleista djalonensis enhances the inhibitory action of GABA, decreases inhibition in neuronal networks, and affects calcium ion transport with low activities on repetitive firing [ 27 , 58 ]. The results indicated that AFAD significantly increased the GABA level in the brain tissue identically to those of sodium valproate administered at a dose of 300 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decoction of Cymbopogon citratus was examined for its phytochemical contents as described previously by Taiwe et al [14] and several families of compounds (alkaloids, glycosides, tannins, flavonoids, triterpenoids, anthraquinones, 7 saponins, phenols) were screened. A comparative thin layer chromatographic study was also performed to screen the presence of bufadienolides in the decoction of Cymbopogon citratus using anisaldehyde sulphuric acid reagent under UV (254 -365 nm) [14].…”
Section: Preliminary Phytochemical Studymentioning
confidence: 99%